Green Hydrogen in Developing Countries - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2020)
In the future, green hydrogen—hydrogen produced with renewable energy resources—could provide developing countries with a zero-carbon energy carrier to support national sustainable energy objectives, and it needs further consideration by policy makers and investors. Developing countries with good renewable energy resources could produce green hydrogen locally, generatingeconomic opportunities, and increasing energy security by reducing exposure to oil price volatility and supply disruptions. Support from development finance institutions and concessional funds could play an important role in deploying first-of-a-kind green hydrogen projects, accelerating the uptake of green hydrogen in developing countries, and increasing capacity and creating the necessary policy and regulatory enabling environment.